Consumption preferences of wild fish and farmed fish: The case of Elazig Province, Turkey - Duman, Muhsine; Dartay, Murside (Ege Univ, Fac Fisheries, 2018)
This study was conducted to determine the preferences of consumers towards culture and wild fish production and their consumption in Elazig. The results are based on data collected by surveys considering households as a basis. It was determined that 96% of the consumers consume fish; 88% prefer wild fish whilst 12% prefer culture fish. Of all, 47% of the consumers who prefer wild fish stated that they prefer wild fish because they are delicious (35%) and healthy and safety (35%) to consume. Those who prefer culture fish (44%) stated that they prefer culture fish as they are always fresh. Although the price is higher than that of culture fish the consumers (70%) are ready to pay extra money to buy wild fish.
Keywords: Wild fish; culture fish; consumption preference; Elazig